Inhibitory Potential of New Phenolic Hydrazide-Hydrazones with a Decoy Substrate Fragment towards Laccase from a Phytopathogenic Fungus: SAR and Molecular Docking Studies - Halina Maniak (MDPI AG, 2021)
Laccase from pathogenic fungi participates in both the delignification and neutralization of phytoantibiotics. Furthermore, it interferes with the hormone signaling in plants and catalyzes melanization. Infections of these pathogens contribute to loss in forestry, agriculture, and horticulture. As there is still a need to expand knowledge on efficient defense strategies against phytopathogenic fungi, the present study aimed to reveal more information on the molecular mechanisms of laccase inhibition with natural and natural-like carboxylic acid semi-synthetic derivatives. A set of hydrazide-hydrazones derived from carboxylic acids, generally including electron-rich arene units that serve as a decoy substrate, was synthesized and tested with laccase from Trametes versicolor. The classic synthesis of the title inhibitors proceeded with good to almost quantitative yield. Ninety percent of the tested molecules were active in the range of KI = 8–233 µM and showed different types of action. Such magnitude of inhibition constants qualified the hydrazide-hydrazones as strong laccase inhibitors. Molecular docking studies supporting the experimental data explained the selected derivatives’ interactions with the enzyme. The results are promising in developing new potential antifungal agents mitigating the damage scale in the plant cultivation, gardening, and horticulture sectors.